A novel expansive soil hardener: performance and mechanism of immersion stability. Issue 47 (27th October 2022) - Mei, Tao; Lan, Jirong; Dong, Yiqie; Zhang, Shanshan; Tao, Huiting; Hou, Haobo
Abstract : Aiming at the existing problems of poor treatment effect and immersion stability of expansive soils, a slag soil hardener (SSH, developed by Wuhan University, China) was combined with different additives to dispose in this study. Abstract : Aiming at the existing problems of poor treatment effect and immersion stability of expansive soils, a slag soil hardener (SSH, developed by Wuhan University, China) was combined with different additives to dispose in this study. The free expansion rate, compressive strength, and immersion stability of samples were compared, and the influences of different additives, curing age, and dry density on the process and mechanism of improvement were discussed. The experimental results indicated that SSH combined with quicklime had the best improvement effect on expansive soils, in which the mass ratio of raw materials was: expansive soil/SSH/quicklime = 92/4/4, and the free expansion rate decreased from 45.90% to 4.4%, compressive strength increased from 2.53 MPa to 6.69 MPa, and there was no splitting after immersion under this ratio. FTIR spectroscopy, XPS and SEM were performed to analyze the characteristic functional groups, structural forms, and morphology of samples to study the mechanism of improvement, which showed that SSH greatly reduced the proportion of montmorillonite in the whole system and further enhanced the mechanism of ion exchange, soil particle connection, and coating protection. The research can provide theoretical reference for engineering the application of expansive soil area in rainy climate and has dual economic and environmental benefits.